Analysis of HbsAg positivity rate before and after vaccination in Turkish and Syrian refugee pregnant women - Ayşe İnci; Doğukan Yıldırım; Kerem Doğa Seçkin; Ali Gedikbaşı (Journal of Infection in Developing Countries)
Introduction: In this study, we aimed to investigate the vaccination rate in Turkish and Syrian pregnant women who gave birth in our hospital, research the difference before and after vaccination, compare these results with other studies conducted in our country and be beneficial to physicians in the follow up of this patient group, who we started to encounter rather frequently in recent months.